Thermal modelling of a totally enclosed fan-cooled electrical machine - La Rocca, Salvatore (2019)
A Totally Enclosed Fan-Cooled (TEFC) low voltage induction motor has been extensively investigated by means of Computational Fluid Dynamics (CFD) in order to look at detailed airflow and heat transfer modelling of such machines. The typical structure of this machine design, where the heat removal is dependent on both the internal and external features, provides a significant modelling challenge as the internal and external flows and heat transfer must be analysed jointly, creating a complex scenario with multiple dependencies. Local fluid flow and thermal investigations of the most critical regions of the internal and external domains respectively allowed the identification of the best modelling approach and optimal mesh settings in terms of solution accuracy and computational cost. A new modelling approach for more realistic end windings representation, which potentially can be applied to different kinds of machines, was developed in order to achieve more accurate predictions of complex fluid flow and heat transfer phenomena compared to a simplified representation commonly used. The developed methodology allowed different levels of end windings porosity to be investigated with results showing a significant impact on overall fluid flow and thermal predictions. A full thermal CFD 3D model of the selected TEFC motor which includes all internal/external fluid and solid domains, in conjunction with electrical/thermal losses distributed across the whole machine, was then developed. The thermal and airflow analysis performed with the CFD conjugate model allowed an accurate understanding and prediction of the overall machine temperature distribution. Experimental tests were carried out to validate the CFD model developed: temperatures, heat fluxes and torque were measured throughout the tests and data collected were compared to quantities predicted analytically and numerically showing a good agreement with predictions. The validation of the developed CFD model allowed also to identify opportunities to improve the machine performance; enhanced cooling can lead to significant improvements in terms of reduction of temperature dependent losses and materials lifetime. Alternative design improvements were therefore proposed to enhance the overall TEFC machine performance and they were investigated with the numerical model developed. Geometrical modifications of the internal original cooling design, consisting of shaft mounted stirrers in the machine’s end region, were considered. The more realistic and detailed end windings representation developed in this work allowed to investigate the impact of higher level of porosity/cavities of the end windings on the overall machine thermal perfomance; results showed how a more accurate and detailed control of the porosity of the end windings can lead to sensible cooling improvements. An alternative external cooling design consisting of a new fan and fan cover was also considered and the impact on the overall machine efficiency was numerically investigated; a 3D printed version of the proposed cooling fan was also manufactured and used for further experimental investigation. The methodology presented in this thesis highlights the capability of CFD to model and simulate very complex geometries and fluid flows, with a high degree of detail and flexibility, allowing accurate predictions of temperature distribution within the electrical machine to be achieved.